EFEK CUSTOMER CUSTOMER INTERACTION TERHADAP SATISFACTION DAN WORD OF MOUTH PADA HOTEL MANDARIN ORIENTAL - Putri Hijir (Jurnal Manajemen dan Pemasaran Jasa, 2015)
The background of this research was the effect of Customer to Customer Interaction affect satisfaction, word of mouth, in mandarin oriental hotel. The objective of this research is to examine the impact of Customer satisfaction, Service Atmosphere, Personal Interaction, Customer Customer Interaction, Word of Mouth. The design of this research applies primary data obtained by distributing questionnaires to 200 customer who are using Mandarin Oriental Hotel. Data analysis method used in this research is Structural Equation Model (SEM). The result of this research there is positive impact Personal Interaction Quality toward customer Satisfaction, there is positive impact Service Atmosphere toward Customer Satisfaction, there is positive impact Service atmosphere toward Customer Customer Interaction, there is positive impact Customer Customer Interaction toward Customer Satisfaction, there is positive impact Customer Customer Interaction toward Word of Mouth, there is positive impact Customer Satisfaction toward Word of Mouth.